Reliability assesment of CNC turning center based on industrial statistics - Mohd Zulfadli, Kamarudin (2010)
Control charts are basic tools in industrial statistics to statistically assess performance-related parameters of a machine or process. The objective of this project is to evaluate the reliability of the CNC machine in the UMP lab using the concept of quality control, namely